Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif